Experimental Study of the Relationship between Slope and Opening Height of OWC Type Wave Breaker Model on Wave Reflection (Zona Laut Jurnal Inovasi Sains Dan Teknologi Kelautan, 2024)
Breakwater is a very effective wave dampening building to be used as a coastal protection against coastal abrasion by destroying wave energy before it reaches the coast. The working mechanism of the OWC type is the rise and fall of ocean waves which will push the air in the OWC column, then will rotate the turbine connected to the generator to produce electricity.This study aims to determine the effect of slope and opening height on breakwater on wave reflection. Then analyze the parameters that affect the amount of wave reflection and compare the resulting wave parameters.This research was conducted at the Hydraulics Laboratory, Department of Civil Engineering, Faculty of Engineering, Hasanuddin University. The method used was experimental based. The resulting wave characteristics consist of three depth variations, three period variations and three stroke variations. The research model used is an Oscillating Water Column (OWC) type breakwater with slope variations of 45°, 60° and 90° and open wall variations as high as 5 cm, 10 cm and 15 cm. The reading of the water level fluctuation is done electronically through the reading of the wave monitor.The results showed that the magnitude of the reflection coefficient is influenced by structural parameters, namely the slope and height of the model opening and hydraulic parameters, namely depth, period and wave height. The effect of the model slope on the reflection coefficient is that the greater the slope, the greater the reflection coefficient value. The effect of the model opening height is that the greater the opening height, the smaller the reflection coefficient value.
Keywords: Breakwater; OWC type Breakwater; Reflection Coefficient